1995
DOI: 10.1002/jts.2490080109
|View full text |Cite
|
Sign up to set email alerts
|

Warzone violence in Vietnam: An examination of premilitary, military, and postmilitary factors in PTSD in‐patients

Abstract: The impact of childhood victimization and other premilitary factors on warzone abusive violence was examined with 177 Vietnam combat veteran inpatients. Premilitary and military variables were also examined in relationship to postmilitary variables, including violence and PTSD. Statistical analyses showed that none of the premilitary variables predicted warzone violence. High combat exposure did, however, predict warzone abusive violence and PTSD. In addition, participation in warzone violence predicted postmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 27 publications
5
45
1
Order By: Relevance
“…In one study of Vietnam veterans, guilt was the most prominent predictor of suicide attempts, over and above PTSD symptom severity and depression (Hendin & Haas, 1991). Similarly, a strong relationship between atrocity involvement and hostility (Strayer & Ellenhorn, 1975) has been found, as have associations between involvement in wartime atrocities and postmilitary acts of interpersonal violence (Beckham et al, 1997; Hiley-Young et al, 1995). …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In one study of Vietnam veterans, guilt was the most prominent predictor of suicide attempts, over and above PTSD symptom severity and depression (Hendin & Haas, 1991). Similarly, a strong relationship between atrocity involvement and hostility (Strayer & Ellenhorn, 1975) has been found, as have associations between involvement in wartime atrocities and postmilitary acts of interpersonal violence (Beckham et al, 1997; Hiley-Young et al, 1995). …”
Section: Introductionmentioning
confidence: 96%
“…In turn, participation in wartime atrocities has been linked with increased suicidal ideation (Braš et al, 2007; Hiley-Young et al, 1995; Maguen et al, 2011; Maguen et al, 2012; Sher, 2009), with depression and PTSD symptoms partially mediating that link (Maguen et al, 2011). In one study of Vietnam veterans, guilt was the most prominent predictor of suicide attempts, over and above PTSD symptom severity and depression (Hendin & Haas, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…[13,[15][16][17][18][19] Some have earlier hypothesized that combat-related guilt may mediate the relation between participation in and/or having witnessed combat-related abusive violence and PTSD or other trauma-related psychopathology. [1,4,20] Importantly, no earlier study has directly examined the mediation hypothesis. In this study, we hypothesized that combat-related guilt would mediate the association between exposure to combatrelated abusive violence and the presence of both PTSD and Major Depressive Disorder (MDD) among Vietnam Veterans.…”
mentioning
confidence: 96%
“…A previous study found that this measure yielded internally consistent scores and was positively associated with PTSD severity. In addition, scores on this measure have been found to be positively associated with both combat exposure and post-military violence against self, spouse, and others (Hiley-Young et al, 1995). This instrument was available for 154 participants in the validation sample and 149 participants in the crossvalidation sample.…”
Section: Combat Exposure Scale (Ces)mentioning
confidence: 98%
“…In order to measure participation in or witnessing of abusive violence (i.e., witnessing or participating in the hurting, killing, or mutilation of Vietnamese), a 6-item subscale from the Vietnam Era Stress Inventory was administered (Hiley-Young, Blake, Abueg, Rozynko, & Gusman, 1995). Frequency of each event was rated as never (did not occur), rarely (once every month), occasionally (once every 2 weeks), often (one or two times each week), or very often (three or more times a week).…”
Section: Combat Exposure Scale (Ces)mentioning
confidence: 99%